2015
DOI: 10.1007/s10494-015-9625-1
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Cycle LES Simulations of a Direct Injection Natural Gas Engine

Abstract: In this work the flow field evolution, mixture formation and combustion process in an engine with methane Direct Injection (DI) is investigated using Large Eddy Simulations. The supersonic methane injection is modeled according to Müller et al. (2013) and combustion by a level set approach. The flame propagation showed to be dependent on the grid resolution. Higher grid resolutions have two opposing effects: first the fraction of unresolved turbulence is reduced, which decrease the flame speed and second flame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…Naturally, regardless of the model, the flame wrinkling under high pressure cannot be resolved on LES meshes which must be compensated for. In this regard, also Schmitt et al [32] observed a strong impact related to the estimated turbulent flame speed utilized for the G-Equation approach. As explained in Section 3.2.2 and Fig.…”
Section: Pressure Curve and Model Sensitivitymentioning
confidence: 94%
See 2 more Smart Citations
“…Naturally, regardless of the model, the flame wrinkling under high pressure cannot be resolved on LES meshes which must be compensated for. In this regard, also Schmitt et al [32] observed a strong impact related to the estimated turbulent flame speed utilized for the G-Equation approach. As explained in Section 3.2.2 and Fig.…”
Section: Pressure Curve and Model Sensitivitymentioning
confidence: 94%
“…Accordingly, the majority of SI engine simulations employ LES combustion models that have already been established in this regard within other applications. Specifically, numerous works use the Flame Surface Density (FSD) approach [30,31], the G-equation [32], the Artificially Thickened Flame (ATF) model [33] and also a few applications based on Probability Density Functions (PDF) [34,35] exist.…”
Section: Chaomentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of these challenges, there have been several numerical studies in recent times where multicycle LES has been used to predict CCV in engine-like geometries and understand the causes for CCV. These include simplified geometries resembling piston and/or valve motions [9][10][11][12][13], realistic engine geometries under motored [14,15] and fired conditions [16][17][18]. Moureau et al [9] performed 2D and 3D LES of multiple cycles of a simplified square piston engine and compared the simulation results with experimental PIV measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Within ICE simulations [22] the models are chosen according to the physics required for the given combustion mode. Accordingly, for spark ignition engines usually the Flame Surface Density (FSD) approach [23,24], the G-equation [25], or the Artificially Thickened Flame (ATF) model [26] are employed to treat the flame propagation. For applications with auto-ignition different mechanisms are dominating [2] and those simulations often use Probability Density Functions (pdf) to account for the unresolved scalar distribution and accordingly obtain a more accurate evaluation of the non-linear relations.…”
Section: Introductionmentioning
confidence: 99%